Theory and Modeling of Slab Waveguide Based Surface Plasmon Resonance - Amnah Hasan; Razi Al-azawi; Ali Alwahib (Engineering and Technology Journal, 2022)
The current study proposes a developing surface plasmon resonance (SPR) sensor that has been widely employed to detect viruses, such as environmental analytes, biological and chemical analytes, and monitoring and medical diagnostics. Optical waveguides have much potential for developing new chemical and biological sensors. Graphene is the world's most vital substance and can be used to enhance other materials. A composite silver film-based SPR sensor with the waveguide. To enhance the silver film's stability, detect the best thickness with the best resonance using different types of analyte: air than 1.1, 1.2, 1.3, and water. The resonance wavelength numerically calculated, loss, sensitivity, Figure of merit FOM, and Refractive index using Lumerical FDE. The numerical data showed the differences in the electric field of SPR in the number of refractive indexes after applying the silver coating layer, and the performance parameters improved. Moreover, Graphene has much promise, yet almost most of it is still unexplored. The fundamentals of graphene-based waveguides and devices were investigated using two layers with FDE. The primary purpose of this study is to show the effective thickness of the Graphene and the analyte's refractive index to get high absorption.